Pegylated Interferon-α Modulates Liver Concentrations of Activin-A and Its Related Proteins in Normal Wistar Rat - Bassem Refaat; Adel Galal El-Shemi; Ahmed Mohamed Ashshi; Elaf Wael Mahamid; Noha Mohammed Al-Qadi (Mediators of Inflammation)
Aims. To measure the expression of activin βA-subunit, activin IIA and IIB receptors, Smad4, Smad7, and follistatin in the liver and the liver and serum concentrations of mature activin-A and follistatin in normal rat following treatment with pegylated interferon-α (Peg-INF-α) and ribavirin (RBV). Materials and Methods. 40 male Wistar rats were divided equally into 4 groups: “control,” “Peg-only” receiving 4 injections of Peg-INF-α (6 µg/rat/week), “RBV-only” receiving ribavirin (4 mg/rat/day) orally, and “Peg & RBV” group receiving both drugs. The expression of candidate molecules in liver was measured by immunohistochemistry and quantitative PCR. The concentrations of mature proteins in serum and liver homogenate samples were measured using ELISA. Results. Peg-INF-α  ± RBV altered the expression of all candidate molecules in the liver at the gene and protein levels P<0.05 and decreased activin-A and increased follistatin in serum and liver homogenates compared with the other groups P<0.05. There were also significant correlations between serum and liver activin-A and follistatin. Conclusion. Peg-INF-α modulates the hepatic production of activin-A and follistatin, which can be detected in serum. Further studies are needed to explore the role of Peg-INF-α on the production of activins and follistatin by the liver and immune cells.